Development of molecular tools for optimisation of C1 gas fermentation in acetogens - Rowe, Peter (2018)
Access to renewable energy and reduction of carbon emissions represent two major issues facing humankind in the twenty first century and beyond. The underlying driving forces behind both are multi-faceted and often intrinsically connected, ranging from environmental concerns over climate change to improving economic security through self-sustaining energy production. Possible solutions to reliance on non-renewable, carbon-emitting fossil fuels have been explored over recent decades, with significant interest placed on biofuels. Due to ease of integration into liquid-based petrochemical fuel infrastructure, these renewable alternatives have been a consistent topic of both industrial and academic interest. Despite offering renewable energy, conventional crop-based biofuel production has faced criticism due to consumption of land, water and other resources associated with agriculture. Acetogens provide a solution to conventional biofuel production due to their utilisation of carbon monoxide and carbon dioxide gas as carbon and energy sources, rather than plant matter. This allows generation of a range of chemical products from a broad range of sources, including industrial waste gases and gasified solid waste. Acetogens offer the double benefit of both renewable energy production, and carbon emission sequestation. This study outlines the development of genetic tools to provide a foundation for using synthetic biology approaches to improve performance of acetogens as industrial chassis. Specifically, development of tools and techniques for the acetogen Clostridium autoethanogenum are described, with further applications of such technology to other Clostridia.